PENERAPAN TEORI SOSIAL DALAM MENUMBUHKAN AKHLAK ANAK KELAS I MADRASAH IBTIDAIYAH NEGERI 1 REJANG LEBONG - YANTO, MURNI; SYARIPAH, SYARIPAH (Universitas Islam Negeri Raden Intan Lampung, 2017)
AbstrakThis research is a field research with qualitative approach. Data were obtained through interviews aimed at principals and teachers. Observation to obtain data by observing directly the process of learning and documentation to obtain information related to madrasah. The results showed that first, the concept of social learning theory has been practiced in Madrasah Ibtidaiyah Negeri 1 Rejang Lebong, which is doing the learning process through imitation. The process of observing and imitating the behavior and attitudes of others as a model is an act of learning. Second, growing the morality of madrasah Ibtidaiyah children using various methods. methods include exemplary methods, habituation, story. Third, the factors that influence the morale of the students are influenced by the age of the child, talents, interests and environment. Fourth Implementation of learning process in social learning theory is through phase of attention, retention phase, reproduction and motivation phase. The authors hope in this study is the need for emphasis on good cooperation between parents, educational institutions, and the public in education, especially in the effort to nurture the childKeywords: Social Learning Theory, Growing, Child Morals.